Draping test with polygonal sample-holding table for measuring the shape-changing ability of sheet-like, bendable by gravity materials - Marianna Halász; Zsolt Borka; Gabriella Oroszlány (Discover Applied Sciences)
Abstract Draping is a 3-dimensional, complex shape change caused by gravity. It characterizes the ability of the given sheet-like material, often textiles, with low bending stiffness to adapt to the shape of an object in a complex way, and therefore, knowing it is important, especially from the point of view of simulating the behaviour of this material. In a draping test, a circular sample is placed on a circular sample-holding table, its edges are allowed to bend down, and then the draping coefficient and the number of waves are calculated based on its planar projection. However, both factors have a large standard deviation, and strangely, the number of waves is not unambiguous. In our research, we replaced the circular table with regular, polygonal sample-holding tables of 3–15 corners, which had the same area, and investigated how the number of table corners is related to the draping coefficient and the number of waves. We compared the results obtained on the polygonal sample-holding tables with the results measured on the circular table. In our article, we present the course of the research, the testing equipment and how we changed it, the tested 7 types of fabrics, and the results obtained. Our results prove that with the use of a polygonal sample-holding table, the number of waves can be clear, the size and arrangement of the waves can be uniform, and so the uncertainty of the measurement results can be reduced, and the repeatability of the test can be improved. Based on the data, the regular six-sided sample-holding table can be recommended for the drape test; only very rigid samples cannot follow its corners with their waves, and the draping coefficient is almost the same as that measured on a round table. The optional use of the hexagonal sample-holding table can be recommended, especially for comparative testing of fabrics for the same purpose, for example, when it is necessary to select in terms of draping the most suitable fabric from among the possible ones for a specific garment or even for a curtain.